2012
DOI: 10.1152/jn.00072.2012
|View full text |Cite
|
Sign up to set email alerts
|

NMDAR antagonist action in thalamus imposes delta oscillations on the hippocampus

Abstract: Work on schizophrenia demonstrates the involvement of the hippocampus in the disease and points specifically to hyperactivity of CA1. Many symptoms of schizophrenia can be mimicked by N-methyl-d-aspartate receptor (NMDAR) antagonist; notably, delta frequency oscillations in the awake state are enhanced in schizophrenia, an abnormality that can be mimicked by NMDAR antagonist action in the thalamus. Given that CA1 receives input from the nucleus reuniens of the thalamus, we sought to determine whether an NMDAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 69 publications
11
74
0
2
Order By: Relevance
“…Since interneurons play important roles in the regulation of oscillations (Jonas et al 2004;Somogyi and Klausberger 2005;Klausberger 2009), it is noteworthy that low frequency (≤ 2 Hz) RE input is also able to drive interneurons in distal radiatum (Dolleman-van der Weel et al 1997) that inhibit both pyramidal cells and other inhibitory interneurons. Driving these particular radiatum interneurons may thus provide a possible mechanism for RE to impose a slow oscillation on CA1 cells, as previously reported by Zhang et al (2012). RE-induced oscillatory activity in CA1 may be in synchrony with slow oscillations in mPFC.…”
Section: Functional Relevancesupporting
confidence: 64%
“…Since interneurons play important roles in the regulation of oscillations (Jonas et al 2004;Somogyi and Klausberger 2005;Klausberger 2009), it is noteworthy that low frequency (≤ 2 Hz) RE input is also able to drive interneurons in distal radiatum (Dolleman-van der Weel et al 1997) that inhibit both pyramidal cells and other inhibitory interneurons. Driving these particular radiatum interneurons may thus provide a possible mechanism for RE to impose a slow oscillation on CA1 cells, as previously reported by Zhang et al (2012). RE-induced oscillatory activity in CA1 may be in synchrony with slow oscillations in mPFC.…”
Section: Functional Relevancesupporting
confidence: 64%
“…NMDA receptor channel blockers have additional neurophysiological effects, including induction of an increase in delta power (Dworak et al, 2011;Kiss et al, 2013;Zhang et al, 2012). In the present study, the higher doses of ketamine increased delta power both in the cortex and hippocampus during both drug-on and drug-off periods.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, the higher doses of ketamine increased delta power both in the cortex and hippocampus during both drug-on and drug-off periods. Mechanisms underlying changes in delta power are not fully understood; previous studies analyzed acute, short-time effects of ketamine on EEG, demonstrating a transient increase in delta power (Fu et al, 2008;Zhang et al, 2012). Therefore, late-onset increase in delta power could be a rebound effect in response to sleep deprivation induced acutely by administration of NMDA receptor antagonists (Kocsis, 2012b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the PFC and MD are the predominant sites mediating the actions of non-competitive NMDAR antagonists, including changes in neurotransmission and behaviour (Amargós-Bosch et al 2006;López-Gil et al 2007;Kargieman et al 2007;Zhang et al 2009Zhang et al , 2012Santana et al 2011;Kiss et al 2011;López Hill and Scorza 2012). Furthermore, it has been proposed that PCP acts on the cortico-thalamo-cortical circuit involving the PFC, RS 15 and thalamus (Celada et al 2013).…”
Section: Pcp-induced C-fos-ir In the Pfc And MDmentioning
confidence: 99%